Unintended Impacts of Collaborative Robots on Social Relations at Work - Regin Öborn, David; Palm, Kristina; Rosengren, Calle; Håkansta, Carin (Nordic Journal of Working Life Studies, 2025)
In light of the growing use of collaborative robots in workplaces, this article investigates how they reshape workplace dynamics and have unintended impacts on the psychosocial work environment and social interactions—issues central to the Nordic model of ‘good work’. This article builds on qualitative interviews from three workplaces in Sweden: a mechanical workshop, a university laboratory, and restaurants in an amusement park. To interpret the findings, we apply Collins’s theory of interaction rituals. While robots were introduced to reduce physical strain, they initially also generated enthusiasm, learning, and ergonomic relief. Over time, however, they contributed to job intensification, additional tasks, and fewer opportunities for spontaneous interaction. The study contributes to debates on robot–human relations and interaction rituals by showing how robots can energize or disrupt social interactions, providing insights into the theoretical understanding and the practical implementation of social robots in the Nordic work context.